The archaeology of childhood and adolescence in the American experience - Baxter, Jane Eva 1971- (University Press of Florida, 2019)
This book is a synthesis of current archaeological and historical work on children in the American past from the 17th through the 21st centuries
Includes bibliographical references and index
Keywords: Geschichte 1600-2000; Children -- United States -- History; Children -- United States -- Social life and customs; Social archaeology -- United States; Soziale Situation; Kind; USA